Community Learning Motivation to Join the School Package C Equivalently High School Education (Research at Foundation PKBM Imam Syafe'i, Bandung) - Lamhot Naibaho; Demsy Jura; Afdaleni Afdaleni (HK-Publishing, 2022)
AbstractEducation is one of the most important things in people's life. But to be able to carry out an education well, of course everyone and even society must have certain obstacles. Even these obstacles can make someone and society who want to be educated stop in the middle of the road. Dropout cases are getting bigger and bigger in the community, the occurrence of dropping out of school is certainly caused by several factors and backgrounds. The interesting thing is that when these factors and backgrounds have occurred, they can again generate motivation to learn in the community. And the people's motivation to learn also occurs because of two things. Namely because of intellectual or material reasons alone.Keywords: Education, Motivation to Learn and Drop Out of School. AbstrakPendidikan merupakan salah satu hal terpenting dalam kehidupan manusia. Namun untuk dapat menyelenggarakan suatu pendidikan dengan baik, tentunya setiap orang bahkan masyarakat pasti memiliki hambatan tertentu. Bahkan rintangan tersebut dapat membuat seseorang dan masyarakat yang ingin dididik berhenti di tengah jalan. Kasus putus sekolah semakin besar di masyarakat, terjadinya putus sekolah tentunya disebabkan oleh beberapa faktor dan latar belakang. Hal yang menarik adalah ketika faktor dan latar belakang tersebut terjadi, maka dapat kembali membangkitkan motivasi belajar di masyarakat. Dan motivasi belajar seseorang juga terjadi karena dua hal. Yaitu karena alasan intelektual atau materi semata.Kata kunci: Pendidikan, Motivasi Belajar dan Putus Sekolah